Study the Serum IL-6 Level between Rheumatoid Arthritis Patients and Control - Semaa Abdulrahman Shaban (Tikrit Journal of Pure Science, 2023)
This study involved (50) patient’s that complaining rheumatoid arthritis from both genders (7 females and 43 males). Their ages range from (26-68) years there are taken from hospitals and clinics, in addition to the control which involve (30) person that look normal and their ages ranges from (23-54).